2022
DOI: 10.1111/cas.15510
|View full text |Cite
|
Sign up to set email alerts
|

LRFN2 binding to NMDAR inhibits the progress of ESCC via regulating the Wnt/β‐Catenin and NF‐κB signaling pathway

Abstract: As a neuronal transmembrane protein, leucine‐rich repeat and fibronectin type‐III domain‐containing protein 2 (LRFN2) can recruit and combine with N‐methyl‐d‐aspartate receptors (NMDARs) to promote nerve growth. Genetic studies suggest that mutations in LRFN2 are associated with various cancers. However, the role and mechanism of LRFN2 in the progression of ESCC have not been elucidated. In this study, we demonstrated that LRFN2 was significantly downregulated in ESCC tissues by qRT‐PCR and immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Sustained activation of β-catenin leads to the continuous self-renewal and growth of tumor cells and is associated with therapeutic resistance [ 17 , 18 ]. Some studies have suggested that the β-catenin signaling pathway plays a key role in promoting the proliferation of ESCC cells [ 20 ]. The regulatory relationship between SAA1 and β-catenin in tumors has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Sustained activation of β-catenin leads to the continuous self-renewal and growth of tumor cells and is associated with therapeutic resistance [ 17 , 18 ]. Some studies have suggested that the β-catenin signaling pathway plays a key role in promoting the proliferation of ESCC cells [ 20 ]. The regulatory relationship between SAA1 and β-catenin in tumors has not been reported.…”
Section: Introductionmentioning
confidence: 99%